THE IMPORTANCE OF IMPLEMENTATION FOREIGNER REPORTING APPLICATION (APOA) IN ORDER TO IMMIGRATION CONTROL TO FOREIGNERS - Bima Yosua A Tarigan; Faridh Al Wajidi; K Karina (Polteknik Imigrasi, 2020)
Immigration control is an activity of collecting, processing, and presenting immigration data and information in order to ensure compliance with immigration laws. Foreigner Reporting (APOA) is an innovation of the Directorate General of Immigration in the implementation of immigration control which is oriented towards the function of law enforcement and state security. However, there are still some obstacles and constraint in the implementation of reporting foreigners through APOA. The formulation of problems examined in this paper is how the implementation of immigration control, reporting procedures, and constraints and obstacles in the implementation of reporting through APOA. This writing uses a qualitative research method with a qualitative descriptive approach through data collection by identifying laws and regulations and collecting some library materials relevant to the topic of this research. From the research results, it was found that there were still many inn owners or managers and the community who had not reported the presence of foreigners in their area. In this case, the Directorate General of Immigration must be able to optimize the implementation of reporting on foreigners so that it makes it easier for immigration officers to carry out immigration control, especially for foreigners.